Dramatic regression of coronary artery stenosis three years after diagnosis. (October 2015) - Narayan, P; Khetan, A
While strategies for the prevention of the progression of coronary artery lesions have been proposed, documentation of the regression of significant coronary artery lesions is rare. Lifestyle modifications and exercise have been reported to influence the regression of coronary disease, but a dramatic disappearance of coronary artery lesions demonstrated angiographically has been rarely reported. We describe a case where diet and lifestyle modifications, along with lipid-lowering therapy, led to the significant regression of coronary artery stenosis.